Acetic Acid-Promoted Rhodium(III)-Catalyzed Hydroarylation of Terminal Alkynes - Duan, Chang-Lin; Liu, Xing-Yu; Tan, Yun-Xuan; Ding, Rui; Yang, Shiping; Tian, Ping; Lin, Guo-Qiang (Synlett, 2019)
Rhodium(III)-catalyzed hydroarylation of terminal alkynes has not previously been achieved because of the inevitable oligomerization and other side reactions. Here, we report a novel Cp*Rh(III)-catalyzed hydroarylation of terminal alkynes in acetic acid as solvent to facilitate the C–H bond activation and subsequent transformations. This reaction proceeds under mild conditions, providing an effective approach to the synthesis of alkenylated heterocycles in high to excellent yields (31–99%) with a broad substrate scope (37 examples) and good functional-group compatibility. In this transformation, the loading of the alkyne can be reduced to 1.2 equivalents, which indicates the significant role of HOAc in lowering the reaction temperature and suppressing the oligomerization of the terminal alkyne. Preliminary mechanistic studies are also presented.
Keywords: acetic acid; rhodium catalysis; hydroarylation; alkynes